The Fact of Training Management at College Level in Meeting Human Resource Requirements of Enterprises in Vietnam (World Journal of Vocational Education and Training, 2021)
The purpose of this research is to find out the fact of training management at college level in meeting the human resource requirements of enterprises in Vietnam. Questionnaire survey method was applied for 3 groups of respondents, including the quantitative (390 questionnaires) and the qualitative (18 interviews) in the northern, central and southern regions. Gathered data were processed using SPSS 22.0 software with tools: Cronbach’s alpha to assess the reliability; EFA to measure the (convergence or discriminant) validity; Descriptive Statistics to rank the level of vocational training at college level so as to meet the human resource needs of enterprises. The study demonstrates the limitations of training management at college level to meet the needs by analyzing the current situation of: (i) planning for training process; (ii) conducting; (iii) monitoring and supervising; (iv) improving and developing; (v) controlling context. This is also the basis for proposing specific solutions in the following research.